2012
DOI: 10.1155/2012/135187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Administration of Human Umbilical Cord Blood Stem Cells in 3-Acetylpyridine-Lesioned Rats

Abstract: Cerebellar ataxias include a heterogeneous group of infrequent diseases characterized by lack of motor coordination caused by disturbances in the cerebellum and its associated circuits. Current therapies are based on the use of drugs that correct some of the molecular processes involved in their pathogenesis. Although these treatments yielded promising results, there is not yet an effective therapy for these diseases. Cell replacement strategies using human umbilical cord blood mononuclear cells (HuUCBMCs) hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 79 publications
2
12
0
Order By: Relevance
“…MSCs were found to prevent the overexpression of GFAP in cerebellum. This reduced GFAP protein levels and immune reactivity in the cerebellum suggests that grafted cells could be involved in the modulation of astrogliosis [31].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…MSCs were found to prevent the overexpression of GFAP in cerebellum. This reduced GFAP protein levels and immune reactivity in the cerebellum suggests that grafted cells could be involved in the modulation of astrogliosis [31].…”
Section: Discussionmentioning
confidence: 97%
“…So, they can be the future form of treatment to bypass the blood brain barrier. Calatrava-Ferreras et al [31] reported HUCBMCs reached the cerebellum and brain stem of rats. They added that, grafted cells reduced neuronal loss, prevented cerebellar glial reactivity and hence, improved motor coordination in ataxic rats.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The rats were divided equally into three groups (n=6): sham-operated (SHAM), ovariectomized (OVX), and OVX + hUCB-MSCs. The OVX + hUCB-MSCs group received an injection of 4.5 x 10 6 hUCB-MSCs dissolved in 250 μL PBS on the tail vein two months after ovariectomy for four consecutive weeks (twice in a week) (Calatrava-Ferreras et al, 2012). However, both SHAM and OVX groups were injected with vehicle (PBS) only.…”
Section: Animals and Experimental Ethicsmentioning
confidence: 99%
“…Intravenous administration of mesenchymal stem cells in ataxic mice has shown that they can rescue the degenerating cells with the help of neurotropic factors such as NGF, BDNF and NT-3 by integrating into the central nervous system [25]. Another study in the rat model demonstrated that intravenous administration of human umbilical cord blood stem cells (HuUCBMCs) reduced neuronal loss and upregulated the expression of proteins critical for cell survival [26]. Clinical studies with BMMNCs showed efficacy in delaying the progression of cerebellar ataxia supported by improvements in various outcome measures such as the Berg Balance Scale (BBS), activity of daily living scale (ADL) and International The objective of our study was to evaluate the safety, feasibility, and efficacy of autologous BMMNCs in the treatment of patient with sensory ataxia.…”
Section: Resultsmentioning
confidence: 99%